Alternatively activated macrophages at the recipient site improve fat graft retention by promoting angiogenesis and adipogenesis. Issue 11 (16th May 2022) - Li, Ye; Chen, Xinyao; Liu, Lin; Chen, Yunzi; Bi, Xin; Chen, Yuting; Zou, Jialiang; Wang, Zijue; Dong, Ziqing; Lu, Feng
Abstract: The inflammatory response mediated by macrophages plays a role in tissue repair. Macrophages preferentially infiltrate the donor site and subsequently, infiltrate the recipient site after fat grafting. This study aimed to trace host‐derived macrophages and to evaluate the effects of macrophage infiltration at the recipient site during the early stage on long‐term fat graft retention. In our novel mouse model, all mice underwent simulated liposuction and were divided into 2 groups. The fat procurement plus grafting (Pro‐Grafting) group was engrafted with prepared fat (0.3 ml). The pro‐Grafting+M2 group was engrafted with prepared fat (0.3 ml) mixed with 1.0 × 10 6 GFP+M0 macrophages, and then, 2 ng IL‐4 was injected into the grafts on Day 3. In addition, 1.0 × 10 6 GFP+M0 macrophages were injected into the tail vein for tracing in the Pro‐Grafting group. As a result, GFP+macrophages first infiltrated the donor site and subsequently infiltrated the recipient site in the Pro‐Grafting group. The long‐term retention rate was higher in the Pro‐Grafting+M2 group (52% ± 6.5%) than in the Pro‐Grafting group (40% ± 3.5%). CD34+ and CD31+ areas were observed earlier, and expression of the adipogenic proteins PPAR‐γ, C/EBP and AP2 was higher in the Pro‐Grafting+M2 group than in the Pro‐Grafting group. The host macrophages preferentially infiltrate the donor site, and then, infiltrate the recipient site after fat grafting. At the early stage, an increase in macrophages at the recipient site may promote vascularization and regeneration, and thereby improve the fat graft retention rate.